Photography as a Copyright Work - Brankov, Boba (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Abstract: The original holder of copyright has moral rights and property rights according to the law. Photograph can be regarded as copyright work, if it meets the criteria stipulated by the legal definition of copyright work: a photo must be created by a human being, it must have a spiritual content, spiritual content above must have the appropriate form and must be an original work. Committee on Constitutional and Legislative Affairs in January 2016 submitted to the National Assembly of the Republic of Serbia a proposal to adopt authentic interpretation of the provisions of article 2, paragraph 2 of Copyright Law. The purpose of this proposal is that each routinely made photo, which is downloaded in digital form, can not be considered as a copyright work. The proposal of the authentic interpretation above is the motive of this article. This work is focused on the elements of photograph as copyright work, copyright infringement due to unauthorized use of photographs, with special reference to the infringement of copyright through social networks.